Training for Better Decisions: Designing a Computer-mediated Distance Education Subject for Tribunal Members - Pamela O'Connor; Beth Gaze (Legal Education Review, 2002)
[Extract] In 1991 Carrie Menkel-Meadow argued that even when law teachers think they are teaching law, they cannot avoid teaching legal ethics as well. “By the very act of teaching, law teachers embody lawyering and the conduct of legal professionals” and give students implicit messages about appropriate lawyering. What, then, do we teach when we do explicitly set out to teach legal ethics? Should we merely expect students to learn some rules and laws that apply to the conduct of legal practice? Can we really expect students to learn to be more ethical in a university course? Should we expect them to learn moral judgment? Perhaps we should be teaching them the skills of legal practice? The depressing conclusion in much of the scholarly literature is that, even as we try to teach our students ethics, they often learn only to become even more cynical about the possibility of ethical practice. They are doubtful that learning ethical rules will accomplish anything; they are disengaged from ethical theory and turned off by courses that seem to focus only on critique of the profession’s failures and problems that appear to be without solutions.